Increasing Entrepreneurship Competency Through Digital Marketing Training for the Entrepreneurs in Malaysia - Hadjri, Muhammad Ichsan; Isnurhadi; Siregar, Lina Dameria; Mulyadi; Yaacob, Zulnaidi (Global Writing Academica Researching & Publishing, 2023)
Currently, digital marketing is very important for the growth of businesses and companies. This is of course very relevant considering that currently the number of internet users is increasing. It is felt that digital marketing can help business owners reach customers more easily, increase sales, and make branding easier for all types of businesses (both small and large scale). Internet technology is an instrument that can promote business effectively and efficiently and help business sustainability because it allows businesses to reach a wider market share and this is done quickly. Responsive digital marketing has enabled business owners to promote their products online. The advantages of digital marketing for businesses and companies encompass effortless connectivity with online consumers, enhanced sales conversions tailored to specific target audiences, cost-effective marketing expenditures, real-time consumer service capabilities, and the capacity to augment the sales efficacy of their products. The participants for this community service activity are the entrepreneurs in Malaysia. The number of participants in this community service activity is 30 people in Balik Pulau Area, Penang, Malaysia. Most entrepreneurs in the Balik Pulau Area, Penang, Malaysia have not done digital marketing. They do not have social media to do digital marketing yet. After carrying out community service activities, entrepreneurs already have social media and understand the basics of digital marketing, especially using social media to market their products.